Development of a Capsule Robot for Exploring the Colon - Gao, Jinyang (Micromachines (Basel), 2019)
A tether-less inchworm-like capsule robot (ILCR) is promising to enable a non-invasive exploration of the colon, while existing ILCRs show barely satisfactory movement performance because the colon environment is nonstructural. In this current study, we develop an enhanced ILCR based on a design rule of maximizing the achievable periodic stroke and minimizing the body length, with the aim of improving movement performance. By designing an axial compact expanding mechanism (EM), employing a novel linear mechanism (LM), and integrating a hollow-cylinder-like power source based on wireless power transmission (WPT), the enhanced ILCR achieves a periodic stroke of 38 mm within a small body length of 33 mm. Our experiments show that the EM and LM can work reliably in an ex-vivo colon with a lot of intestinal mucus, and the power source can safely supply a stable working voltage of 3.3 V even in the worst case. Being wirelessly controlled and powered, the enhanced ILCR shows satisfactory movement performance, with velocities of 15.8 cm/min, 12.1 cm/min, and 7.4 cm/min in a transparent tube, a tiled colon, and a suspended colon, respectively, promising to accomplish an exploration for the 1.5-m long colon within 30 min.